The BBNJ clearing-house mechanism: considerations for its diverse functions, users, and sources - Gaebel, Christine; Harden-Davies, Harriet; Vierros, Marjo Kristiina; Caldeira, Mariana; Coelho, Luciana; Hassanali, Kahlil; Sekinarai, Alumita; Schütz Veiga, Júlia (Frontiers in Ocean Sustainability, 2025)
Adopted in 2023, the Agreement for the Conservation and Sustainable Use of Biological Diversity of Areas beyond National Jurisdiction (BBNJ Agreement) is a significant milestone for multilateralism and is expected to promote a more holistic and cooperative approach to biodiversity governance. Central to realising these ambitions, however, is the necessity for the best available science, knowledge, and information to inform and guide implementation. To support and facilitate the sharing of science, knowledge, and information, the BBNJ Agreement establishes a Clearing-House Mechanism (ClHM). Importantly, the ClHM is envisioned to play an integral and multifaceted role across the implementation of the BBNJ Agreement. It is to serve as a central data, knowledge, and information repository hosting data, information, and documents relating to the four elements under the Agreement, namely Marine Genetic Resources, Area-Based Management Tools, Environmental Impact Assessments, and Capacity-Building and the Transfer of Marine Technology. Moreover, it is to facilitate and advance data sharing and collaboration, act as a hub to match capacity development needs with opportunities, and more. The multifaceted functions, wide scope of information, and diversity of end-users of the BBNJ ClHM, highlight the intricate but critical task of designing and operationalising a fit-for-purpose ClHM for biodiversity of areas beyond national jurisdiction. Here, we aim to provide insights on what this might entail. Through a comprehensive analysis of the envisioned functions of the ClHM and an exploration of lessons learned from existing mechanisms and databases, we identify and discuss key considerations which are critical for implementing and operationalising a fit-for-purpose BBNJ ClHM.